UNDERSTANDING TRANSITIONAL ADMINISTRATION UNDER INTERNATIONAL LAW - Upadhyay, Santosh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study acknowledges this situation as “transitional administration” in a broader term just to connote the transitory nature of such administration in context of time, administering actors and their purposive character under international law. It is important to note that these perceived end results of such administrations have always been heavily influenced by the temporal undercurrents of dominant rationalities and objectivities of world politics. This paper engages itself with these rationalities and objectivities in order to unravel their biases. While doing so, the study uses the framework of international law